Green Simplistic Biosynthesis of AntiBacterial Silver Nanoparticles Using Annona Squamosa Leaf Extract - Singaravelu Senthamilselvi; Ponnuchamy Kumar; Alagiyamanavalan Lakshmi Prabha; Munisamy Govindaraju (Nano Biomedicine and Engineering, 2013)
Green nanotechnology involves the synthesis of nanoparticles without the involvement of toxic chemicals. The present study reports the green synthesis of silver nanoparticles from Annona squamosa leaf extract rapidly within 20 min. High throughput characterization such as UV-vis spectroscopy, Fourier Transform-Infrared Spectroscopy (FT-IR), Transmission Electron Microscopy (TEM), Field Emission-Scanning Electron Microscopy (FE-SEM), X-ray diffraction (XRD) and Zeta potential measurements disclose the existence of silver nanoparticles. The phenolic compounds present in the aqueous leaves extract paves way for the possible reduction of silver to nano-silver. Electron microscopic studies revealed the average size of nanoparticles were 52 nm. The nanoparticles are highly stable by reaching a zeta potential value of −33.6 mV. Comparative antibacterial efficacy of silver nanoparticles was investigated by disk diffusion and microtitre broth dilution method against Escherichia coli. The result showed that silver nanoparticles are toxic to E. coli cells at higher concentration. Overall, we suggest microtitre broth dilution method is more reliable to determine the antimicrobial activity of silver nanoparticles than disk diffusion method.